THE INFLUENCE OF THE ROLE OF MIDWIVES IN REDUCING ANXIETY DURING THE DELIVERY PROCESS AT HADI HUSADA HOSPITAL - Fahnidar Rahma, SKM, M.KM; Ririn Anggriani Sitorus (Cattleya Darmaya Fortuna, 2025)
Anxiety during labor can disrupt the smoothness of the labor process and increase the risk of complications. The role of midwives in providing emotional support, information, and assistance is expected to reduce this anxiety. The objective is to analyze the influence of the midwife's role on reducing maternal anxiety during the labor process. The method is a quantitative descriptive correlational study with a total sampling technique. The sample consisted of 32 midwives and 32 mothers giving birth. Data were collected using a questionnaire (Guttman scale for the role of midwives and the HARS scale for anxiety), analyzed univariately and bivariately (chi-square test). The results are that 90.6% of midwives play a supportive role. The level of maternal anxiety is dominated by mild anxiety (46.9%), no anxiety (40.6%), and moderate (12.5%). The chi-square test shows a significant relationship between the midwife's role and the level of anxiety (p = 0.010). The conclusion is that the supportive role of midwives (emotional support, information, and assistance) significantly reduces maternal anxiety during labor. Optimizing the role of midwives is recommended to improve the quality of midwifery services.